2023
DOI: 10.3748/wjg.v29.i21.3341
|View full text |Cite
|
Sign up to set email alerts
|

Lumen-apposing-metal stent misdeployment in endoscopic ultrasound-guided drainages: A systematic review focusing on issues and rescue management

Abstract: BACKGROUND The introduction of lumen-apposing metal stents (LAMS) for endoscopic ultrasound (EUS)-guided drainages has marked a turning point in the field of interventional ultrasound and it is gathering worldwide diffusion in different clinical settings. Nevertheless, the procedure may conceal unexpected pitfalls. LAMS misdeployment is the most frequent cause of technical failure and it can be considered a procedure-related adverse event when it hampers the conclusion of the planned procedure or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Postoperative clip displacement can lead to various complications, such as rectal elevated lesion caused by Hem-o-lok clip migration after prostate cancer surgery, abscess in the fallopian tube caused by Hem-o-lok clip migration after laparoscopic appendectomy, and dysphagia caused by Hem-o-lok clip migration into the esophagus subsequent to clamping of the azygous vein after radical resection of distal esophageal cancer[ 6 - 8 ]. LC and laparoscopic common bile duct exploration (LCBDE) are the most effective way to treat gallbladder stones, gallbladder polyps, and cholecystitis[ 9 , 10 ]. Hem-o-lok clips are commonly utilized for clamping the arteries and ducts of the gallbladder during LC and LCBDE.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative clip displacement can lead to various complications, such as rectal elevated lesion caused by Hem-o-lok clip migration after prostate cancer surgery, abscess in the fallopian tube caused by Hem-o-lok clip migration after laparoscopic appendectomy, and dysphagia caused by Hem-o-lok clip migration into the esophagus subsequent to clamping of the azygous vein after radical resection of distal esophageal cancer[ 6 - 8 ]. LC and laparoscopic common bile duct exploration (LCBDE) are the most effective way to treat gallbladder stones, gallbladder polyps, and cholecystitis[ 9 , 10 ]. Hem-o-lok clips are commonly utilized for clamping the arteries and ducts of the gallbladder during LC and LCBDE.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review [87] reported a 2.0% frequency of LAMS misdeployment during EUS-guided PFC drainage. Distal flange misdeployment in the peritoneal cavity, external to the cystic wall, was reported in up to 36.1% of cases, managed in most cases with over-the-wire placement of a new stent (LAMS, SEMS, or double pigtail stents/plastic) through the novel fistula tract as a rescue therapy.…”
Section: Lams-related Adverse Events In Pfc Managementmentioning
confidence: 99%
“…A recent review of LAMS misdeployment revealed an overall misdeployment rate of 5.8% after EUS-CDS, mostly of the distal flange [15]. Such misdeployments are usually associated with small-diameter CBDs (<15 mm).…”
Section: Expected Early Adverse Eventsmentioning
confidence: 99%